Identification Of Readiness Factors For The Agile Erp ASSESSMENT - Santo Fernandi Wijaya, Harjanto Prabowo, Ford Lumban Gaol; Meyliana (International Journal of Control and Automation, 2020)
The impact of adopting technological innovation for industries will require management’s commitment make changes to business processes in order to accomplish the work to be more efficient and effective. Enterprise Resource Planning (ERP) system is one solution to improve work efficiency and effectiveness. The purpose of ERP implementation is to enhance business value and organizational agility. The fact that implementation failure is still an issue that needs to be considered seriously. For this reason, it is necessary to evaluate of the readiness level to accept the ERP system as a necessity for supporting organizational operations. This is a challenge for the authors to analyze the gaps in ERP implementation by focusing on the ERP readiness assessment. The purpose of this research is to identify of ERP readiness factors as a measurement tool before management decides to implement ERP. This research methodology uses the Smart PLS Square Equation Modeling approach as a tool for processing data from questionnaire statements. The result of this research is the development of a methodology for evaluating the ERP readiness assessment for industry.